GEOTECHNICAL ASSESMENT OF SOME FAILED SECTIONS ALONG GOMBE-POTISKUM HIGHWAY; NE-NIGERIA - A. SULAIMAN; K M.OJO; M.A.SADIQ; E. Y., MBIIMBE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The research is focused on soil samples obtained from some failed sections along Gombe –Potisk un Road the area of investigation is between Doho to Tongo, kwami L.G.A. Gombe State of abo ut 17 to 62km. The engineering properties of soils were investigated by conducting laboratory tes t and compared with standard in which six sample pits were dug and samples were collected for geotechnical determination. Soils taken at Doho were treated as sub-base material while those ta ken from other points were treated as sub-grade materials. The results obtained from the geotech nical tests performed indicate that the MDD ranges from 1.400 to 1.97gm/cm3 the OMC has the maximum result of 24% and minimum value of 7.9% for compaction and moisture content. The soils recorded 0% and 13% as the minimum and maximum CBR values after 24 hours (sub-base) and 48 hours (sub-grade) soaking respectively. The test conducted revealed that maximum value of 76.0% and 38.5% and minimum value of 12.3% were obtained for liquid limits (LL%) and th e plasticity index of the samples ranges from 11.2% to 53.3%. The soils were classified as GM, ML and S because of variations in properties and different points of sampling. The soil samples from Doho is made up of sandy materials (inorganic) and are seen as suitable engineering materi als while those obtained at Tongo where the road terribly failed composed mainly of shale, silt (o rganic) mixed with small gravels are unsuitable materials.